Integrasi Nilai-Nilai Karakter dalam Kurikulum PAI Berbasis Deep Learning untuk Siswa Sekolah Dasar - syahrul aziz; M. Choirul Muzaini (MGMP PAI SMP BINTAN, 2026)
Abstract This study aims to analyze the integration of character values into the Islamic Religious Education (PAI) curriculum based on deep learning for fourth-grade students at SD Negeri 3 Mataram Udik. The research employed a qualitative approach with a case study design. The participants included one PAI teacher and 46 students divided into two classes. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that character value integration was implemented through three main dimensions of deep learning: mindful learning, which fostered self-awareness and moral reflection; meaningful learning, which connected instructional content to students’ real-life experiences to strengthen value internalization; and joyful learning through STEAM-based projects that enhanced creativity, collaboration, and responsibility. The integration of these approaches not only improved students’ conceptual understanding of religious content but also holistically developed character traits such as honesty, trustworthiness, discipline, empathy, and teamwork. This study contributes to the development of a deep learning-based PAI instructional model aligned with 21st-century educational demands while maintaining strong religious value foundations.